Luminescence Studies on Thallium doped RbBr-RbI Mixed Crystals - S. Nagarajan2; R. Ravisankar3, P. Eswaran1, (Recent Research in Science and Technology, 2011)
Photoluminescence (PL) studies of RbBr1-xIx: Tl+ (0.1mol %) with x = 0.00, 0.05 and 0.10 mixed crystals grown in vacuum is reported at room temperature. PL emission spectra of the mixed crystals excited in the A-absorption band of RbBr:Tl+ exhibited an asymmetric emission band with peak 3.34eV, which is the characteristic emission bands of Tl+ ions in RbBr: Tl+. When excited in the low energy tail of A-band absorption, additional emission bands were observed. The photoluminescence emission bands slightly shifted towards the low energy side with increasing iodine composition x.